THE USE OF SCRATCH CODING-BASED GAMES AS AN INNOVATIVE MEDIUM TO INCREASE STUDENTS' MOTIVATION TO LEARN MATHEMATICS - Adhi Wibawa, Gandung; Rohmanuddin Ahmad; Erna Yayuk (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyse the effectiveness of using Scratch coding-based learning media in increasing primary school students' motivation to learn mathematics. The study used a qualitative descriptive approach with six fourth-grade students from MI IT Nurul Iman Punung as subjects. Data were collected through observation, practical tests, and questionnaires assessing aspects of attention, active participation, perseverance, confidence, and enjoyment of learning. The results showed that the use of Scratch significantly increased the motivation to learn mathematics in all students. Male students excelled in programming logic and technical exploration, while female students excelled in visual creativity and social collaboration. An important finding from this study is that Scratch-based learning is able to create an interactive, enjoyable, and meaningful learning atmosphere, thereby changing students' perceptions of mathematics from a difficult subject to an interesting and contextual activity. The conclusion of the study confirms that Scratch is effective as an innovative learning medium for fostering intrinsic motivation, logical thinking, and creativity in students in 21st-century learning.